Assessing the efficiency of Ateel wastewater treatment station and its suitability for rehabilitation improving water quality and its safe and practical application - Houshia, O.J.; Boufaroua, M.; Alimari, A.; Souqia, N. (2013)
In regions where water is in short supply, wastewater treatment offers the possibility for the efficient removal of unwanted pollutants and germs so that the water may be used for irrigation. Water scarcity is an old problem in Palestine because of various geographical settings and political turbulence. The problem is compounded by population growth and development. As a result of the increasing demand for water, using alternative options has become a must to meet water needs. The demand for water can be reduced by increasing the efficiency of water use and by making usable sources of water previously considered unusable. One possible supply is wastewater. This project sets out to treat and reclaim wastewater as a supply of irrigation water and thus enhance crop production. The project results reveal that wastewater from the Ateel wastewater station potentially can be used for irrigating crops. It offers many social and financial benefits for improving the farmers sources of revenue. Various parameters were monitored and measured for the Ateel wastewater station and yielded some interesting and promising data.